ChemInform Abstract: A Facile Route for the Synthesis of Novel Heterocyclic Prostaglandin F2α Analogues. Issue 3 (January 2015) - Shankar, M.; Mohan, H. Rama; Prasad, U. Viplava; Harikrishna, M.; Rao, M. P. Pareswar; Ravindra, A.
Abstract A general method for the preparation of heterocyclic prostaglandins with variations in the ω‐side chain is presented.